Fractal correlations and linear analyses of heart rate variability in healthy young people with different levels of physical activity. (2nd October 2019) - Moraes, Íbis A. P.; Silva, Talita D.; Massetti, Thais; Menezes, Lilian D. C.; Ribeiro, Vivian F.; Tropiano, Ligia M. C. C.; Barnabé, Viviani; Hoshi, Rosangela A.; Monteiro, Carlos B. M.; Fernandes, Marcelo
Abstract: Changes in cardiac autonomic regulation, expressed by increased sympathetic activity and decreased heart rate variability, have an important relationship with the onset of lethal cardiac phenomena. Therefore, we aimed to evaluate the cardiac autonomic behaviour in young people according to their level of physical activity. Through the International Physical Activity Questionnaire, 55 healthy young non-smokers with no history of previous diseases and whose parents did not suffer from metabolic syndrome were assessed and divided into groups: sedentary (n=12), insufficiently active (n=16), active (n=14), and very active (n=13). We collected respiratory rate, systolic and diastolic blood pressure at rest, and body mass index. Subjects remained supine at rest, and without mental stress for 15 minutes in a controlled environment. Using a cardiofrequency meter (Polar ® RS800CX), data were analysed in the time domain, frequency domain, and detrended fluctuation analysis. For the sedentary group, the mean RR and rMSSD were significantly lower, and the insufficiently active group showed higher means, but significantly only for rMSSD. The insufficiently active group showed in the detrended fluctuation analysis that α2 was significantly lower compared with the sedentary, active, and very active groups. We conclude that young, healthy, sedentary individuals present an increased heart rate and that insufficiently active individuals present a decreased fractal correlation and increased parasympathetic activity.